Immunological, Serological and Hematological Changes in COVID 19 Patients of Dhaka City - Akter, Amena; Biswas , Bishyajit Kumar; Bepary, Sukumar (Jagannath University Journal of Science, 2024)
The analytical test reports of COVID-19 patients admitted in two major hospitals in Dhaka City were analyzed to observe the immunological, serological and hematological abnormalities that can be significant for managing the patients in emergencies. The observed levels of ferritin, procalcitonin, D–Dimer, C-reactive protein (CRP), creatinine and alkaline phosphatase (Alkp) were taken into consideration for this study. Though these parameters were elevated as mentioned for patients from many other countries, in significant cases, the values were normal or even lower than the normal levels. The ferritin level was normal (For men, 24 to 336 micrograms per liter. For women, 11 to 307 micrograms per liter) in only 30% of the patients, whereas, 50% of the patients had higher values and 20% patients had the lower values. Similarly, the procalcitonin (normal value 0.1 to 0.5 ng/mL) level was found to be normal in only 27% of the patients while remaining 73% patients had the high level of this parameter. The D‑Dimer level (less than 0.50) was also found to be normal in only 27% of the patients, whereas 72% of the patients had the higher levels. The C‑reactive protein was within the normal level in only 22% of the patients, whereas, 76% of the patients had the high level of this marker. The creatinine was found to be increased in 60% of the patients. There were 88% patents having increased levels of Alkp with only 12% patients having normal levels. Thus, the elevations of the immunological, serological and hematological parameters were somehow different from those observed from patients in other countries. This information might be useful in managing the hospitalized COVID-19 patients in our country. Jagannath University Journal of Science, Volume 11, Number 1, June 2024, pp. 203−207